Penerapan Metode Rad Pada Implementasi Sistem Informasi Pelayanan Kesehatan Berbasis Website Studi Kasus Klinik Sritina Cikarang Barat - Arif Tri Widiyatmoko; Sriyati Asni (DPPM Universitas Pelita Bangsa, 2025)
Information systems play an important role in facilitating human work across various sectors, including companies, government agencies, organizations, and healthcare services. In the healthcare sector, particularly in clinics, information systems help manage service processes and administrative tasks more effectively and efficiently. However, patient services at Sritina Clinic are still not optimal, resulting in relatively low service quality. This condition highlights the need to develop a better and more user-friendly system to improve overall performance. The main problem addressed in this study is how to design and build a website-based Clinic Service Information System that can make service activities easier, faster, and more efficient. The system is expected to streamline administrative processes, reduce errors in data management, and improve the quality of patient services. The purpose of this research is to develop a website-based clinic information system that enhances healthcare services for the community in a more practical, quick, and efficient manner. The results show that the developed website can provide essential clinical service information, including patient data, polyclinic data, patient medical records, and polyclinic queue data, thereby supporting improved service quality at Sritina Clinic.